Feature recognition patterns for form features using boundary representation models - Ismail, N.; Abu Bakar, N.; Juri, A.H. (Springer-Verlag London, 2002)
This paper present a new method for automatic form feature recognition from boundary representation of a solid model. The proposed method is called the edge boundary classification technique. This technique uses the geometry, topology, and spatial information of a solid model for feature recognition patterns. Some aspects of edge boundary classification are discussed for recognising non-intersecting and intersecting form features.